Performance and Reliability Assessment of the APS 2.0 Pneumatic Safety System for Fuel Tank Tanker Operations on Inclined Road Conditions - Syafrie, Muh.; Ilyas Wirawan, Radithya; Hidayah Toufan, Fandy; Agung Apriyanto, Taufik (Jurusan Pendidikan Teknik Elektro, 2026)
Fuel tanker trucks operating on inclined roads face high safety risks owing to potential rollback events that can cause accidents, infrastructure damage, and fires. This study evaluated the performance, reliability, and feasibility of the Automatic Parking Safety (APS) 2.0 system, a pneumatic preventive device designed to mitigate rollback risks. The system integrates a pneumatic wheel chocking mechanism with dual sensors (inclination and motion) to improve activation accuracy and prevent false triggering, offering a physical restraint solution that is beyond the capabilities of conventional brake-based hill-start assist systems. An applied experimental method was used, including material compliance testing, pneumatic performance testing (6–8 bar), system integration, inclined road simulations, and three months of field monitoring. The results show stable performance without leakage, an average response time of ±3 s, consistent operation over repeated cycles, 100% activation accuracy under hazardous conditions, and zero accidents during the field evaluation. These findings indicate that the APS 2.0 is a feasible, safe, and reliable preventive system for tanker truck operations on inclined roads.